Exploration of learner-content interactions and learning approaches: The role of guided inquiry in the self-directed online environments. (March 2022) - Al Mamun, Md Abdullah; Lawrie, Gwendolyn; Wright, Tony
Abstract: The dramatic increase in the prevalence of hybrid and online learning environments, in part due to the growth in blended learning pedagogies and more recently the impact of the COVID-19 pandemic, has intensified the focus on developing instructional strategies that support student learning in self-directed online environments. One particular education research context is in the design of online environments that can support guided inquiry-based learning in the absence of the teacher. Specifically, how embedded pedagogy facilitates students' interactions with the online learning content and influences their engagement and approaches to learning. This study investigates the nature of student interactions with learning content in an online, guided inquiry-based, self-directed learning environment to explore their approaches to learning. Students interacted with scaffolded guided-inquiry online modules designed through application of a predict-observe-explain-evaluate framework. Quantitative data (engagement measures) were collected through digital artifacts and qualitative data (student reflections and activity) through interviews and student written responses. A diversity in learning approaches was observed as a result of individual learners' differences in their prior online experiences and existing chemistry knowledge. Learners' individual differences also influenced student engagement in terms of persistence, systematic investigation and understanding of the science concepts. Findings from this study contribute to understanding the nature and diversity in student interactions that inform the instructional design of self-directed online environments. Graphical abstract: Image 1 Highlights: Students are provided online learning modules in a self-directed environment. Students' approaches to learning are investigated during the learner-content interaction. Prior online experience influences students' behavioural effort. Prior subject knowledge influences students' cognitive effort.